Política fiscal y gasto social en el Perú: ¿cuánto se ha avanzado y qué más se puede hacer para reducir la vulnerabilidad de los hogares? - Castro, Juan Francisco (2008)
This paper analyzes the relationship between fiscal policy and social expenditure coverage during the different phases of the economic cycle, and sheds some light on the determinants of household vulnerability in Peru. Results for the 1994-2004 period reveal that the positive relation between total spendingand growth has contributed to the procyclicality of social expenditure. In fact, its coverage (social spending per poor) falls more than 4% for each 1% reduction in per capita GDP. Thus, a counter-cyclical fiscal rule could help protect social expenditure coverage during recessions, but this would solve only part of theproblem. Empirical evidence regarding the relation between consumption and income variations reveals that poor household face severe restrictions to smooth consumption across the different states of nature, and that social programs now in place have only a marginal contribution reducing these disparities.Thus, a counter-cyclical fiscal rule should be accompanied by intervention aimed at providing those assets that foster consumption smoothing. In this way, more households would be able to attain and secure a consumption level above the poverty line. On this regard, empirical evidence provided herehighlights the importance of education and access to external remittances as important mechanisms to reduce consumption volatility.​